(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This scientific article explores the conceptualization of chemistry terminology in the French and Uzbek languages, aiming to shed light on the linguistic and cultural nuances that shape the understanding of scientific concepts in these two languages. The study employs a comparative analysis to examine how key chemistry terms are translated and conceptualized in French and Uzbek, considering the influence of linguistic structures, cultural contexts, and historical developments on the representation of scientific ideas.